Aktivitas Antidiare Seduhan Kayu Secang (Caesalpinia sappan L.) Pada Mencit (Mus musculus) - Parawansah P (Universitas Bhakti Kencana, 2015)
Sappan (Caesalpinia sappan L.) is one of the plants that has efficacy in treating some diseases. One of them is as an antidiarrheal. The nature of the Caesalpinia sappan are adstringens which can relieve diarrhea with intestinal mucous membrane collapse. The purpose of this study was to determine the effect of antidiarrheal of C.sappan steeped and to know how much concentration that has an effect as an antidiarrheal in mice. The type of this research was experimental study consisting of five treatments with three repetitions. Research carried out by observing the frequency of diarrhea to change to be normal feces after oral administration with C.sappan steeped with a concentration of 1%, 2%, 3%, Loperamideas a positive control, Na CMC as a negative control and the time of observation for 10 hours.The results showed that C.sappan steeped showed the most good antidiarrheal effect that was at a concentration of 2% b/v with an average frequency of bowel movements as much as 1.6 times. Anova statistical analysis results showed that the data hypothesis was accepted or there were significant differences between treatment groups. This research concluded that C. sappan steeped could give antidiarrheal effects that accelerated the changes of feces consistency to be normal.